Bullying Victimization at School and Headache: A Meta‐Analysis of Observational Studies. Issue 6 (2nd April 2014) - Gini, Gianluca; Pozzoli, Tiziana; Lenzi, Michela; Vieno, Alessio
<x xml:space="preserve">Abstract</x> Background and objectives Being bullied at school is a risk factor for a variety of negative consequences, including somatic problems. The purpose of this meta‐analysis is to determine the association between peer victimization and headache in the school‐age population. Methods A systematic literature search was conducted in September 2013 to identify observational studies that examined the association between being bullied and headache in children and adolescents. Odds ratios (OR) were pooled by using a random‐effects model. Moderator and sensitivity analyses were conducted. Results Twenty studies, including a total of 173, 775 participants, satisfied the pre‐stated inclusion criteria. Fourteen studies reported data on the prevalence of headache, which was on average 32.7% (range: 9.1‐71.7%) in the bullied group and 19.1% (range: 5.3‐46.1%) in the control group. Two separate meta‐analyses of the association between being bullied and headache were performed on 3 longitudinal studies (OR = 2.10, 95% confidence interval = 1.19‐3.71) and 17 cross‐sectional studies (OR = 2.00, 95% confidence interval = 1.70‐2.35), respectively. Results showed that bullied children and adolescents have a significantly higher risk for headache compared with non‐bullied peers. In the cross‐sectional studies, the magnitude of effect size significantly decreased with the increase of the proportion of female participants in the study sample. No further moderators were statistically significant. Conclusions The positive association between bullying victimization and headache was confirmed. Further research on the environmental factors that may influence this symptom is needed.